Sposoby wykorzystania odnowień brzozy brodawkowatej Betula pendula Roth do przebudowy na obszarach po rozpadzie drzewostanów świerka pospolitego Picea abies (L.) H. Karst. w Beskidzie Śląskim - Ambroży, Sławomir; Chomicz-Zegar, Elżbieta; Kapsa, Mariusz; Vytseha, Ruslan; Zachara, Tadeusz (Leśne Prace Badawcze, 2017)
One of the tree species appearing after a decline of Norway spruce Picea abies (L.) H. Karst. in the Silesian Beskid Mountains is Silver Birch Betula pendula Roth. Therefore our study was aimed at evaluating this birch regeneration and the dynamics of changes resulting from experimental cutting. Measurements and inventories of trees were conducted on research plots located in a ten-year old birch regeneration site with either no cutting, partial cutting (50%) or clear cutting (100%) of birch. We observed an introduction of biocenotic species (rowan, willow, aspen) as well as the target species (spruce, fir, beech) under the birch canopy. Fir and beech were also planted, because of their slow natural regeneration. The clear cut treatment caused a great number of sprouts growing from birch stumps, reaching a height of about 2 m over 3 years, resulting in competition with the regeneration of other species. Partial cutting did not cause such a drastic amount of sprouting. Furthermore, we found that only the spruce height increment is significantly less under a birch canopy compared to open space. The obtained results indicate a necessity to adjust the density and species composition of regenerating tree species under a birch canopy, avoiding complete removal of the first generation birch cover and the need to moderately thin out birch.